Entrepreneurial Orientation and New Venture Performance: The Moderating Role of Intra- And Extraindustry Social Capital - Stam, Wouter; Elfring, Tom (Academy of Management Journal, 2008)
This study advances research on entrepreneurial orientation and social capital by examining how the configuration of a founding team's intra- and extraindustry network ties shapes the relationship between entrepreneurial orientation and new venture performance. Using an original data set of 90 new ventures in the emerging open source software industry, we found that the combination of high network centrality and extensive bridging ties strengthened the focal link. Among firms with few bridging ties, centrality weakened the relationship between entrepreneurial orientation and performance. Overall, these findings contribute to a better understanding of when network centrality represents an asset or a liability for entrepreneurial firms.